Factors Affecting English Teachers’ Participation in Guru Penggerak Program at Jambi City - Siregar, Rossa Aprilia; Masbirorotni, Masbirorotni; Sartika, Delita (Universitas Jambi, Magister Program of English Education Department, 2024)
This study explores the factors affecting English teachers' participation in Guru Penggerak program at Jambi City. Using Kyriacou and Kobori's motivation framework, it identifies intrinsic, extrinsic, and altruistic factors that affect teachers' decisions in participating the Guru Penggerak Program. Qualitative approach was used, with semi-structured interviews conducted with five junior high school English teachers. The findings of this study reveal there are 6 Intrinsic factors; Aspire to enhance personal and professional growth, develop connections and friendships, the program is manageable to follow, curiosity, desire to take on a leadership role and inspire students, develop effective teaching strategies and gain a deeper student’s undertstanding. There are 6 Extrinsic factors; Instruction from the principal, encouragement from principals, family support, availability of career levels, opportunities, and benefits, recognition of the guru penggerak certificate. There are 3 Altruistic factors; the desire to positively impact students, improve English learning engagement, and share knowledge with others.